Upacara Pemakaman Ngutang Mayit Kepercayaan Masyarakat Trunyan Bangli - Yuli Juniari, Ni Wayan; Widyawati, Anak Agung Ayu Alit (Jayapangus Press, 2021)
The Hindu-Trunyan religious beliefs in Trunyan Village, Bali, differ from the Balinese Hindu religion in celebrating important ceremonies such as Galungan, Kuningan, Nyepi, Ciwaratri, Sarasawati, and Pagarwesi, which are generally carried out by Hindus in Bali. In contrast, Trunyan Hindus hold important ceremonies unique to themselves or may not even celebrate at all. The research method in this literature study is library research, which involves collecting data from various library sources such as books, encyclopedias, documents and scientific journals. The funeral ceremonies in Trunyan Village are divided into three locations, namely Sema Wayah, Sema Nguda, and Sema Bantas, which are differentiated based on the circumstances of a person's death, not based on their social status or position.